Calcium looping sorbents for CO2 capture - Erans Moreno, Maria; Manovic, Vasilije; Anthony, Edward J. (Elsevier, 2016)
Calcium looping (CaL) is a promising technology for the decarbonation of power generation and carbon-intensive (cement, lime and steel) industries. Although CaL has been extensively researched, some issues need to be addressed before deployment of this technology at commercial scale. One of the important challenges for CaL is decay of sorbent reactivity during capture/regeneration cycles. Numerous techniques have been explored to enhance natural sorbent performance, to create new synthetic sorbents, and to re-activate and re-use deactivated material. This review provides a critical analysis of natural and synthetic sorbents developed for use in CaL. Special attention is given to the suitability of modified materials for utilisation in fluidised-bed systems. Namely, besides requirements for a practical adsorption capacity, a mechanically strong material, resistant to attrition, is required for the fluidised bed CaL operating conditions. However, the main advantage of CaL is that it employs a widely available and inexpensive sorbent. Hence, a compromise must be made between improving the sorbent performance and increasing its cost, which means a relatively practical, scalable, and inexpensive method to enhance sorbent performance, should be found. This is often neglected when developing new materials focusing only on very high adsorption capacity.
Keywords: CO2 capture; Calcium looping; Sorbent; Limestone; Synthetic sorbent; Sorbent modification method